Low-temperature thermal expansion of pure and inert gas-doped fullerite C₆₀ - Aleksandrovskii, A.N.; Bakai, A.S.; Dolbin, A.V.; Esel`son, V.B.; Gadd, G.E.; Gavrilko, V.G.; Manzhelii, V.G.; Moricca, S.; Sundqvist, B.; Udovidchenko, B.G. (Физика низких температур, 2003)
The low temperature (2-24 K) thermal expansion of pure (single-crystal and polycrystalline) C₆₀ and polycrystalline C₆₀ intercalated with He, Ne, Ar, and Kr has been investigated using the high-resolution capacitance dilatometer. The investigation of the time dependence of the sample length variations ΔL(t) on heating by ΔT shows that the thermal expansion is determined by the sum of positive and negative contributions, which have different relaxation times. The negative thermal expansion usually prevails at helium temperatures. The positive expansion is connected with the phonon thermalization of the system. The negative expansion is caused by reorientation of the C₆₀ molecules. It is assumed that the reorientation is of a quantum character. The inert gas impurities affect the reorientation of the C₆₀ molecules very strongly, especially at liquid helium temperatures. A temperature hysteresis of the thermal expansion coefficient of Kr- and He-C₆₀ solutions has been revealed. The hysteresis is attributed to orientational polyamorphous transformation in these systems.